Die Entwicklung der Ausdrucksmittel der russischen Praesens- und Praeteritalflexion - Hammel, Robert (Specimina philologiae Slavicae, 1997)
The present work ... is intended to supplement the synchronous descriptions of Slavic verbflexion so far with the so-called "analytic-synthetic-functional method" by a diachronic investigation. She may refer to the preparatory work of T. BERGER (1981a) and W. LEHFELDT (1983a) and wants to build a bridge between the method and the research done in recent decades in the field of diachronic linguistics and the historical Slavic phonology, morphology and accentology.